Heat Shock Responsive Gene Expression Modulated by mRNA Poly(A) Tail Length - Wu, Xuan; Wang, Jie; Wu, Xiaohui; Hong, Yiling; Li, Qingshun Quinn (Frontiers in Plant Science, 2020)
Poly(A) tail length (PAL) has been implicated in the regulation of mRNA translation activities. However, the extent of such regulation at the transcriptome level is less understood in plants. Herein, we report the development and optimization of a large-scale sequencing technique called Assay for PAL-sequencing (APAL-seq). To explore the role of PAL on post-transcriptional modification and translation, we performed PAL profiling of Arabidopsis transcriptome in response to heat shock. Transcripts of 2477 genes were found to have variable PAL upon heat treatments. Further study of the transcripts of 14 potential heat-responsive genes identified two distinct groups of genes. In one group, PAL was heat stress-independent, and in the other, PAL was heat stress-sensitive. Meanwhile, the protein expression of HSP70 and HSP17.6C was determined to test the impact of PAL on translational activity. In the absence of heat stress, neither gene demonstrated protein expression; however, under gradual or abrupt heat stress, both transcripts showed enhanced protein expression with elongated PAL. Interestingly, HSP17.6C protein level was positively correlated with the severity of heat treatment, and peaked when treated with abrupt heat. Our results suggest that plant genes have a high variability of PALs and that PAL contributes to swift posttranslational stress responses.